Characteristic of different level of fermented concentrate in the rumen metabolism based on in vitro - Sari, N. F.; Ridwan, R.; Rohmatussolihat, R.; Fidriyanto, R.; Astuti, W. D.; Widyastuti, Y. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
Digestibility is a description of the ability of feed material that can be utilized by livestock. Higher digestibility of feed material means the total amount of feed content that can be digested in the digestive tract. This study aimed to obtain the proportion of the use of fermentation concentrate in rumen fermentation based on in vitro. The feed used consisted of 7 treatments as follows P1 (20% Pennisetum purpureum: 80% concentrate), P2 (30% P.purpureum : 70% concentrate), P3 (40% P.purpureum : 60% concentrate), P4 (50% P.purpureum : 50% concentrate), P5 (20% concentrate: 80% P.purpureum), P6 (30% concentrate: 70% P.purpureum) and P7 (40% concentrate: 60% P.purpureum). Dry matter digestibility (DMD) and organic matter digestibility (OMD) were done using Theodorou method. Gas production was measured when the samples were incubated at 39oC in the waterbath incubator at hours 2, 4, 6, 8, 10, 12, 24, and 48. Approximately 0.75 g of feed formulation was mixed with 75 mL of rumen fluid buffer. The rumen fluid is taken from 3 fistulated cattles prior to morning feeding. A complete randomized design with three replicates was used. Asymptotic gas production and kinetics were estimated by the Orskov’s model. The results of this study showed that P2 and P3 treatment showed the best digestibility among others treatment with 71.63% ; 71.06% of DMD and 76.42% ; 71.65% of OMD. In conclusion, P2 and P3 treatment can be used as feed for beef cattle.